Komparasi Kinerja Keuangan Bank Umum Dan Bank Syariah Pada Tahun 2007-2010 - Citra Kalyana Utami; Supatmi . (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2012)
This research studies about comparing the performance of syariah banks and conventional banks in Indonesia periods 2007-2010 using eight finansial ratios, i.e. CAR, APB, PPAP, The fulfillment of PPAP, ROA, ROE, NIM, and BOPO. Based on the sampling criteria, there are two sample groups i.e three conventional banks and three syariah banks. The analysis tool used to prove the hypothesis in the research is Mann Whitney U Test. The research result that the financial performance of syariah banks are measured by APB, Fulfillment of PPAP and BOPO have significant different with the financial performance of conventional banks, but there are no different in the financial performance when measured by CAR, PPAP, ROA, ROE, and NIM.Keywords : Financial performance, Conventional bank, Syariah Bank